Dehumidification and thermal regeneration characterization of binary deep eutectic solvents in liquid desiccant air conditioning systems - Oladosu, T.L. (Elsevier Ltd, 2021)
The energy-saving propensity of liquid desiccant air dehumidification technique compared with its counterparts, mitigating the limitations of conventional desiccant solutions and the need for energy optimization in indoor space cooling, has invigorated the exploration of alternative desiccant solutions. This study investigates different binary deep eutectic solvents as a potential alternative working fluids in liquid desiccant air conditioning systems. Hydrogen bond acceptors (Choline chloride, N, N-Diethylethanolammonium chloride, 1-Butyl-3-methylimidazolium chloride, ZnCl2) and hydrogen bond donor (Ethylene glycol) were synthesized in different ratios to form binary deep eutectic solvents. The physiochemical, thermophysical and rheological properties of the investigated solutions were characterized and evaluated. DES A1 (mixture of choline chloride and ethylene glycol in ratio 1:2) and DES D1 (1-Butyl-3-methylimidazolium chloride and ethylene glycol in ratio 1:1) were found best among investigated binary DES solutions. The dehumidification and thermal regeneration potential of these promising solutions were further investigated in a humidity chamber and a drying oven, respectively. At 65 relative humidity, 30 Â°C air temperature, and 3.77 Ã 10â4 m2 moisture-desiccant contact area, the estimated dehumidification mass flux of DES A1 and DES D1 are 4.61 Ã 10â2 and 3 Ã 10â2 g/m2âs, respectively. Empirical correlations obtained for deep eutectic solvents moisture absorption in this study provide an error limit between Â±2.6 to Â±3.5 . These solutions are found promising as alternative solutions for dehumidification and thermal regeneration. Â© 2021